Method and Device for Determining Aspect Angle Progression (2010)
A method and a device are provided for specifying, in the context of the image generation of ISAR processing, the determination of the aspect angle course subject to which the radar illuminates the vehicle during the exposure and subject to which the vehicle echoes are reflected back to the radar. Using the distance between the radar sensor and the vehicle as well as the change in distance, both of which are determined from the radar data, the position and the velocity of the vehicle are determined at any time during the exposure through linkage with available road information. The aspect angle is then determined from the positions of the sensor and of the vehicle as well as from the direction of movement of the vehicle. The required road information can be acquired from digital maps or images (e.g. aerial photographs, SAR-images).